Grumpy Unicorn. Hits the road : a graphic novel - Spiotto, Joey (Graphix, an imprint of Scholastic, 2020)
"Everyone's favorite magical grouch returns in a graphic novel all about adventure! In this collection of laugh-out-loud stories, Grumpy introduces us to his friends like Sassy the Sasquatch and Jack the Jackelope, takes us camping and on road trips, causes a major dust-up at a museum, and more!"--Provided by publisher